Идея света в философии Григория Сковороды: две литературно-музыкальные визии (по произведениях А. Щетинского и Л. Грабовского) - Драганчук, Вікторія Миколаївна; Drahanchuk, Viktoriia M.; Драганчук, Виктория (Akademia Pomorska w Słupsku, 2015)
The musical works on the texts of the leading Ukrainian philosopher H. Skovoroda are investigated in this article. It is argued that Skovoroda was left the commandments of a spiritual-moral self-improvement. The first commandment is a vision of the world order. According to Skovoroda, human as a microcosm has two natures, the external bodily and internal divine. The manifestation of the latter is a meaning of life: to awaken the divine light in itself is „to conquer death”. The second commandment is „the joy of the heart as the light of God’s love”. „Know thyself”, the call indicates the true path of knowledge, because the „inner” human is the seat of the spark of God. These commandments are embodied in the choral symphony „Know yourself” by A. Szczecinskiy and cantata „Temnere Mortem” L. Grabowskiy. The third commandment is „cognation law”. The development respectively to the talent is the key to opening a „inner” human. „Cognation” at the community level is a basis of the nation life – „Everyone must know his people and the people themselves”. This Skovoroda’s commandment until found the display in the literary-musical discourse. It expects an interpretation...
The idea of light in the philosophy of Gregoriy Skovoroda: two literary-musical visions (by the works of A. Szczecinskiy and L. Grabowskiy)
Keywords: літературно-музичний дискурс; literary-musical discourse; заповіді духовно-морального вдосконалення; commandments of a spiritual-moral self-improvement; хорова симфонія; choral symphony; кантата; cantata